МОНІТОРИНГ ПРОЦЕСУ ФОРМУВАННЯ ПРАВОВОЇ КУЛЬТУРИ МАЙБУТНІХ УЧИТЕЛІВ ІСТОРІЇ ТА ПРАВОЗНАВСТВА У ФАХОВІЙ ПІДГОТОВЦІ (World Science, 2020)
The article monitors the process of forming the legal culture of future teachers of history and jurisprudence in professional training, which included analysis of the subjects taught in the educational program in the specialty Secondary Education (History). Jurisprudence, analysis of external and internal factors that influence the process of formation of legal culture. The causes of low formation of legal culture of future teachers of history and jurisprudence are established: low requirements for the process of its formation, legal units within the disciplines of professional training offered to study, presented in the standards of pedagogical specialties autonomously from the legal courses, lack of discretion plan, insufficient legal competence of teachers, which, due to the peculiarities of the content of the discipline, it is necessary to teach the norms of Ukrainian law, professional training of future teachers of history and jurisprudence does not correspond to the level of legal culture, which should be demonstrated by a specialist after graduation from higher education institution. The criteria for selecting the content and volume of legal information needed for future history and law teachers are highlighted.